The Implications of Polygamy on the Demographic Reality in Palestinian Society and the Stance of Israeli Civil Laws Towards It - Abu Freach, Samy Garad (Arab Journal for Sciences and Research Publishing, 2025)
The research aims to study the phenomenon of polygamy in Palestinian society within Israel, focusing on its demographic implications (such as population growth and age structure) and the stance of Israeli laws on the issue. It also seeks to understand the interaction between social, cultural, and civil legal factors in the context of the prohibition of polygamy under Israeli law,The research adopted a descriptive-analytical methodology, analyzing data and information through a review of scientific literature, Israeli laws, and statistics related to the demographic reality of Palestinian society. Key findings of the research include demographic implications, where polygamy contributes to increased population growth rates and changes in the age structure of Palestinian society, which is considered a significant factor in the demographic reality. Additionally, Israeli laws face difficulties in enforcing the prohibition of polygamy due to social and cultural factors, leading to selective enforcement of the law. Palestinian society within Israel is conservative and views polygamy as a means to strengthen demographic presence, while Israeli institutions perceive it as a demographic threat. Accurate data collection and analysis are hindered by the lack of official registration of polygamous marriages to avoid legal repercussions.The research concluded that polygamy reinforces demographic presence by encouraging Palestinian society to continue high birth rates, achieving positive demographic changes. Despite legal pressure, loopholes in the application of Israeli laws are exploited to support polygamy. However, there is a need to raise awareness about the positive demographic implications of polygamy for Palestinian society. Accurate statistics remain difficult to obtain due to the risk of legal consequences under Israeli law.
Keywords: Polygamy; Demographic Reality; Palestinian Society; Civil Laws; Israel